Initial Assessment and Evaluation of Traumatic Facial Injuries - Truong, Tuan A. (Seminars in Plastic Surgery, 2017)
The care of the facial trauma patient continues to evolve in the ever-changing face of medicine. Patients can be reassured that their care is managed by a variety of specialists knowledgeable in the assessment and management of complex facial injuries. Thanks in part to advances in imaging modalities, bone fixation techniques and technology, and a wider array of reconstructive procedures, the foundation upon which the reconstructive ladder of facial injuries rests continues to expand. The overall goal of repair is a return to a preinjury state of form and function.
Keywords: facial trauma; initial assessment; facial evaluation